Neuropsychological profile in adult schizophrenia measured with the CMINDS. Issue 3 (30th December 2015) - van Erp, Theo G.M.; Preda, Adrian; Turner, Jessica A.; Callahan, Shawn; Calhoun, Vince D.; Bustillo, Juan R.; Lim, Kelvin O.; Mueller, Bryon; Brown, Gregory G.; Vaidya, Jatin G.; McEwen, Sarah; Belger, Aysenil; et al.
Abstract: Schizophrenia neurocognitive domain profiles are predominantly based on paper-and-pencil batteries. This study presents the first schizophrenia domain profile based on the Computerized Multiphasic Interactive Neurocognitive System (CMINDS ® ). Neurocognitive domain z -scores were computed from computerized neuropsychological tests, similar to those in the Measurement and Treatment Research to Improve Cognition in Schizophrenia Consensus Cognitive Battery (MCCB), administered to 175 patients with schizophrenia and 169 demographically similar healthy volunteers. The schizophrenia domain profile order by effect size was Speed of Processing ( d =−1.14), Attention/Vigilance ( d =−1.04), Working Memory ( d =−1.03), Verbal Learning ( d =−1.02), Visual Learning ( d =−0.91), and Reasoning/Problem Solving ( d =−0.67). There were no significant group by sex interactions, but overall women, compared to men, showed advantages on Attention/Vigilance, Verbal Learning, and Visual Learning compared to Reasoning/Problem Solving on which men showed an advantage over women. The CMINDS can readily be employed in the assessment of cognitive deficits in neuropsychiatric disorders; particularly in large-scale studies that may benefit most from electronic data capture. Highlights: This study presents the first CMINDS ® battery schizophrenia cognitive domain profile. The schizophrenia profile shows the strongest effect size for speed of processing. Women perform better than men on attention, speed of processing, and verbal learning. Men perform better than women on reasoning. Computerized neuropsychological batteries can be used in neuropsychiatric studies.